2021
DOI: 10.3389/fphys.2021.763711
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Force-Velocity Relationship in Countermovement Jump and Sprint With Approach Jump, Linear Acceleration and Change of Direction Ability in Volleyball Players

Abstract: The force-velocity (FV) relationship allows the identification of the mechanical capabilities of musculoskeletal system to produce force, power and velocity. The aim of this study was to assess the associations of the mechanical variables derived from the FV relationship with approach jump, linear sprint and change of direction (CoD) ability in young male volleyball players. Thirty-seven participants performed countermovement jumps with incremental loads from bodyweight to 50–100 kg (depending on the individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…But this could be justified because, although the horizontal force demands in COD actions are high, gravity always acts in all sporting actions and the vertical force demands could be greater (75). However, previous research has found a relationship between the mechanical variables of the horizontal force-velocity profile (F-Vp) and COD performance in soccer ( r ≤ −0.54; p ≤ 0.03) (76) and volleyball players ( r ≤ −0.42; p < 0.01) (70). Within the horizontal force variables, maximal strength ( r ≤ −0.42; p ≤ 0.02) and power ( r ≤ −0.58; p < 0.01), and the ability to apply horizontal force effectively with a more forward orientation to the ground ( r ≤ −0.54; p < 0.05), correlated most strongly with COD performance.…”
Section: Discussionmentioning
confidence: 99%
“…But this could be justified because, although the horizontal force demands in COD actions are high, gravity always acts in all sporting actions and the vertical force demands could be greater (75). However, previous research has found a relationship between the mechanical variables of the horizontal force-velocity profile (F-Vp) and COD performance in soccer ( r ≤ −0.54; p ≤ 0.03) (76) and volleyball players ( r ≤ −0.42; p < 0.01) (70). Within the horizontal force variables, maximal strength ( r ≤ −0.42; p ≤ 0.02) and power ( r ≤ −0.58; p < 0.01), and the ability to apply horizontal force effectively with a more forward orientation to the ground ( r ≤ −0.54; p < 0.05), correlated most strongly with COD performance.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that a successful COD needs enhanced physical capacities of lower body strength and power (4,7,13,15,18,21,25,32,37,45,47). The results from the research of Banda et al (13) con rmed that possessing a tting level of lower-body power should assist an athlete in rapidly changing direction in reply to the demands of the competition.…”
Section: Relation Between the Fvt And Pro-agility Shuttlementioning
confidence: 97%
“…It has been previously revealed that performance in different types of jumps tests has positive relationships with faster linear and COD in athletic populations (7,13,21,25,47). The FVt, as a strength/power test, utilized the stretch-shortening cycle (SSC) capacities of the lower body, and this is an important quality for speed linear (eg; T 5 , T 10, and T 20 ).…”
Section: Relation Between the Fvt And 20-m Sprintmentioning
confidence: 99%
See 1 more Smart Citation
“…One of our studies reported that approach jump performance was influenced by Pmax (r = 0.53) and F0 (r = 0.51) in sprinting, as well as F0 in jumping (r = 0.45). On the other hand, only the FV variables obtained from sprinting alone contributed to explaining linear sprinting and CoD ability (r = 0.35-0.93) [100]. Marcote-Pequeño et al [92] reported that jump height was strongly correlated with Pmax and moderately with V0 in both jumping and sprinting FV profiles in elite female football athletes, while moderate correlations with F0 were found only in the sprinting FV profile.…”
Section: Force-velocity Relationshipmentioning
confidence: 99%